Dental fluorosis: a review - Rosas López Portillo, Fernando; Rosas Alcaraz, Victor Manuel; Gámez Valenzuela, Jesús; Molina Ángulo, Ingryd Fabiola; Gonzáles Jiménez, Martha Viridiana; Olivas Velázquez, Anel Karely; Reyna Solis, Cinthia Lizbeth; Rocha López, Adelina; Cortina Aguilar, José Aurelio; Villalobos Rodelo, Juan José; Duque-Urióstegui, Cristhal (International Journal of Research in Medical Sciences, 2024)
Ingesting fluoride for prolonged periods or in doses higher than those recommended during enamel formation produces changes from the appearance of very thin white lines to serious structural defects, resulting in a pathological entity known as dental fluorosis. The severity of the changes depends on the amount of fluoride ingested; it is a disease that has an epidemiological behavior with endemic characteristics. The indicated management for TF1 and TF2 lesions is dental whitening or infiltrating resin; for TF3 and TF4 micro abrasion and/or whitening and in TF5 combined technique with macro, micro abrasion and dental whitening. It is essential that public health actions be prioritized to mitigate potential complications due to fluorosis, especially in areas identified as endemic.